Enhancing Student Engagement and Active Participation in Dynamic Electricity Problem-Solving through Problem-Based Learning (PBL) - Cecep Jaya Subagja (PT. Berkah Digital Teknologi, 2023)
Purpose: This study aims to analyse the impact of the implementation of Problem-Based Learning method to the student’s engagement and active participation in class. Research Methodology: This study uses Classroom Action Research with descriptive statistics using the data of student’s engagement and active participation. Results: The application of problem-based learning can increase student’s engagement and active participation in class. Limitations: This study analyses the impact of Problem-Based Learning method in Science Class. Contribution: Problem-Based Learning can be a useful method to increase student’s engagement and active participation in class.